Injuries in water polo - Brooks, J. M. (Clinics in Sports Medicine, 1999)
Water polo is the only true "contact" sport of the aquatic disciplines. This article deals with the most common, aggressive, acute injuries, and the repetitive, overuse strains and sprains facing any athlete. Research to date demonstrates that the combination of swimming and throwing (without the benefit of a firm base of support) places a unique demand on the water polo athlete. The shoulder continues to be the most recognized and studied area of injury, with lacerations and traumatic fractures of the face and hand the next most prevalent. The premiere of women's water polo in the Sydney (Australia) 2000 Olympic games will draw more attention to this exciting, challenging sport.